2016
DOI: 10.2460/javma.249.7.807
|View full text |Cite
|
Sign up to set email alerts
|

Survey of referring veterinarians’ perceptions of and reasons for referring patients to rehabilitation facilities

Abstract: OBJECTIVE To identify patterns of referral to US small animal rehabilitation facilities, document referring veterinarians' perceptions of rehabilitation services, and examine factors that encouraged and impeded referral of veterinary patients to rehabilitation facilities. DESIGN Cross-sectional survey. SAMPLE 461 completed surveys. PROCEDURES Referral lists were obtained from 9 US rehabilitation facilities, and surveys were emailed or mailed to 2, 738 veterinarians whose names appeared on those lists. Data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Although some of the previous studies also used objective data from force platform analysis, conclusions cannot be extrapolated given the difference in the affected joint (stifle), and the primary treatment was surgical, not conservative. Nonetheless, few clinicians are prone to include rehabilitation techniques in the treatment process because of its cost or their lack of knowledge in the field, among others [41].…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the previous studies also used objective data from force platform analysis, conclusions cannot be extrapolated given the difference in the affected joint (stifle), and the primary treatment was surgical, not conservative. Nonetheless, few clinicians are prone to include rehabilitation techniques in the treatment process because of its cost or their lack of knowledge in the field, among others [41].…”
Section: Discussionmentioning
confidence: 99%
“…Consideration in balancing professional clinical rehabilitation with home exercise therapy must be weighed and is often influenced by similar variables to those affecting healthy aging. For example, cost and distance were the two variables most likely to prevent referral of a client seeking a rehabilitation specialist for the pet (102). On the other hand, a study examining outcomes from T3-L3 hemilaminectomies in dogs noted that those receiving rehabilitation had fewer post-operative complications, further supporting the notion that professional physiotherapy allows for closer patient monitoring and timelier intervention (103).…”
Section: • a Combination Of Objective And Subjective Assessmentmentioning
confidence: 99%
“…Since the 1980s, canine physical therapy started to gain clinical attention, and it has demonstrated tremendous scientific advances. One study reported that approximately 70% of veterinarians in United States refer animals for physiotherapy [1].…”
Section: Introductionmentioning
confidence: 99%